The Rate of Postprandial Blood Glucose Decrease, After Mild Interval Physical Exercise - Akhmad Fathoni (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2022)
Physical exercise with a lower intensity is known to lower blood glucose levels. However, interval physical exercise (which is almost close to the situation in everyday society) is still rarely done. The purpose of this study was to determine the difference in the decrease in blood glucose in moderate intensity physical exercise at intervals of 2:3 minutes and 4:6 minutes postprandial. This research is cross-sectional experimental research with the pretest posttest research design. The research sample consisted of 20 high school students, which were divided into 10 people in the 2:3 interval training group and 10 people in the 4:6 interval training group. Samples were selected using purposive sampling. Samples were given exercise in the form of a treadmill in the active phase and leisurely walking in the resting phase. The data collected were blood glucose before exercise (pretest) and after exercise (posttest) in the 22nd minute and 42nd minute. The results of the ANOVA test for changes in blood glucose pre and posttest in the two treatment groups in the 22nd minute showed a value of p=0.001 (p <0.05), while in the 42nd minute p=0.176 (p>0.05). This means that there was a significant difference between the pre- and post-test blood glucose of the two treatment groups at 22 minutes, but there was no significant difference after exercise at 42 minutes.